CREATIVE CLUSTER OR CREATIVE CLASS?: A CASE STUDY OF NITIPRAYAN ARTIST KAMPONG, YOGYAKARTA - , Asmorowati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Florida (2003) states that creative people tend to move to an area with place-related âtalent, technology and toleranceâ that become a creative center. Porter (2000) argues that clusters, or geographic concentrations of interconnected companies and associated institutions in a particular field, linked by commonalities and complementarities. Further, the ongoing process of cooperation and collaboration to solve shared problem result a clustering. The research studies the relevance between the Floridaâs context of creative class and the Porterâs context of creative clusters. The main-research question is: Why has Nitiprayan artist kampong emerged and grown as a creative economy?â Further the research wants to know to what extent the emergence and growth of Nitiprayan artist kampong can be explained with Porterâs context of creative clusters and with Floridaâs context of creative class. This study is an explanatory study as the study is trying to search for the causes and reasons for the phenomenon and its historical background. The research found that Floridaâs theory explains why artists move to Nitiprayan. Amenity, is the most important factor that they looking for. It will create a perfect âhabitatâ for artist to create the art work. They have different lifestyle, such as nightlife and peculiar appearance. A place with openness and tolerance attracts them. Social interaction exist either among the artist and between artists with the local society. Their identity is an artist of Yogyakarta. The natural view, Javanese traditional art and its activities, the authenticity and quality of place, are what make this place more attractive to many artists. It is clearly that Richard Floridaâs theory of creative class giving a powerfull explanation in the process of emerging this creative center. Meanwhile, Porterâs theory of cluster is more relevant to explain the growth of this creative cluster. Quality of place in theory of cluster including natural resources, physical infrastructure, strategy and rivalry. Demand condition is also affecting their decision to choose this place as a place to live except the presence of the buyers that mainly collectors inside or outside Indonesia. Collective action was built among the artists. Trust that includes familiarity grew. Network is very important for developing their career. Legal or contractual security is needed in trading process of the artwork because the product is a very expensive and high-valued commodity. The process is continuing, from forming a creative class to clustering. Clustering become more important. The study results appear that this cluster stage reaching the emerging cluster. Ongoing collaboration or joint project was developed. The weakness form this cluster is the government support. Moreover, firms need to become economically viable. This redirects government support to start to give attention to modern art as well not only to traditional art. The difficulty is to strike a balance: promote clustering without losing the openness. Further, this study reveals that both theories are important and linked.